(untitled) (Vietnam Journal of Community Medicine, 2023)
Introduction and objectives: Transurethral resection of the prostate (TURP) was still the gold standard on management lower urinary tract symptoms (LUTS) in patients with benign prostatic hyperplasia (BPH). The aim of this study was to investigate the results of transurethral resection of the prostate in patients who underwent surgery in 19-8 hospital. Subjects and methods: In this prospective study, we collected datas from 125 cases who underwent TURP from Jan 2021 to Dec 2022 at the Department of Urology, 19-8 Hospital, Ministry of Public Security. Results: The study results showed that the average age was 66,28 ± 8,29. The average prostate weight on ultrasound was 56,97 ± 12,16. The average pre-op and post-op IPSS score was 24,16 ± 4,25 and 6,79 ± 3,17. The average pre-op and post-op QoL score was 5,01 ± 0,89 and 1,88 ± 0,45. Complications after surgery included post-op bleeding in 21 patients (16,8%), urinary incontinence 12 patients (9,6%). 84% patients has good surgical result. 14,4% getting average result and 1,6% with bad result with 2 cases. Conclusions: The results confirmed that Transurethral resection of the prostate (TURP) is an effective treatment for patients with BPH. There was a significant decrease in quality of life and improve lower urinary tract symptoms.